The effects of photoperiod and temperature-related factors on maize leaf number and leaf positional distribution in the field - Xu, Honggen; Ming, Bo; Wang, Keru; Xue, Jun; Hou, Peng; Li, Shaokun; Xie, Ruizhi (Frontiers in Plant Science, 2023)
Quantifying the effects of various environmental conditions on the variation of maize leaf number is essential to estimate maize environmental adaptation and population structure and enhance maize productivity. In this study, three temperate-adapted maize cultivars, differing in maturity classes were sown on eight different dates. Sowing dates ranged from middle and late April to early July covering a wide range of environmental conditions. Random forest regression and multiple regression models with variance partitioning analysis were used to assess the effects of environmental conditions on the number of leaves and their distributions on maize main stems. We demonstrated that TLNs increased in the order of FK139 < JNK728 < ZD958 among the three cultivars, and the variation in TLN for each cultivar were 1.5, 1.76, and 2.75 leaves, respectively. The variation observed of TLN was ascribed to the change in LB and they were higher than the variation of LA. Variations of TLN and LB were mainly affected by photoperiod during the V7 to V11 stage, and sensitivities of TLN and LB to photoperiod range from1.34 to 2.95 leaves h-l. The variation of LA was mainly affected by temperature-related factors. Therefore, the results of this study enhanced the understanding of key environmental conditions to the variation of maize leaf number and providing scientific support for adjusting sowing date and selecting suitable cultivars to mitigate climate change in maize production.